Effect of twin thickness-length ratio on twin-induced dynamic recrystallization of coarse-grained Mg alloys - C Wang; C Xie; P F Xie (Materials Research Express, 2021)
In the current study, based on the disclination quadrupole, the thermodynamic process of the necklace-like TDRX structures with smooth and straight boundaries is theoretically modeled. The influence of the applied shear stress and the twin thickness-length ratio on the misorientation angle between TDRX and matrix grain and the volume ratio of TDRX to parent twin band are numerically analyzed and experimentally validated by the electron back-scatter diffraction characterization. The results show that: (1) the misorientation angle increases with increasing applied shear stress; (2) The greater the thickness-length ratio is, the lower the volume ratio of TDRX to parent twin is; (3) The elevation of the applied shear stress can clearly escalate the volume ratio of TDRX to parent twin. Based on the above results, some strategies regulating TDRX are given based on the control of the applied shear stress and twin thickness-length ratio.